Analytical approach of some legislative texts related to the establishment of professional football in Algeria - LABAR Riad (Journal of Comparative Legal Studies, 2021)
The purpose of this study is to analyze legislative texts governing professional football based on the content analysis method. Despite the legal reforms that followed the post-independence period, the practice of sport has been assimilated to an activity that consumes more resources than it can produce. An attempt to professionalize football was initiated as early as 1999, but this operation did not have the expected effects. In a first step, professionalism in Algeria appeared for the first time with the advent of performance sports associations, which led at some moment the development of Algerian sport. In the second step, a new attempt to apply professionalism has been relaunched to respond to the claims of international sporting institutions, In practice, this process was launched by the Algerian Football Federation in 2010, but up to now there have been several difficulties in its application.
Keywords: Professionalism; Football; Legislative texts; Sport movement